Metode VAT untuk meningkatkan kemampuan berbahasa ekspresif tunarungu di Kabupaten Gowa - Cahaya Cahaya (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
Objective was to determine (a) the application of the method vibration audio tactile (VAT) in improving language skills expressive deaf students in SLB Somba Opu Gowa, (b) the ability to speak expressively before and after the application of the method vibration audio tactile (VAT) students deaf SLB class VIII in Somba Opu Gowa. This research is a kind of experiment subjects tungal (Sangle Subject Researct). This study design is the type A-B-A. Research subjects SMPLB eighth grade students of the Deaf in SLB Somba Opu Gowa. The collection of data obtained through the test works with deskriktif analysis techniques. The results showed that the implementation of the intervention application of audio tactile vibration method (VAT) could increase the ability of class VIII berbahasaekspresif SMPLB deaf in SLB Somba Opu Gowa. Results obtained at baseline phase 1 (A-1) prior to the application of audio tactile vibration method (VAT), and after application of audio tactile vibration method (VAT) or baseline phase 2 (A-2) obtained by ability level value rises 26% or 88% level. The results obtained by the students can be concluded that the application of the method of audio tactile vibration affect the increase in expressive language skills in deaf students in SLB Somba Opu Gowa